Tradition and Traditionalism from the Viewpoint of Fritjhof Schuon and Dr. Nasr - S. Mahdi Emam jome; Zahra Talebi (Comparative Theology, 2012)
Traditionalism that to be put as contemporary progress infront of modernism be liever of live, dynamic and eternal tradition that never lost. It is one unity and manifested in different forms. This meaning of tradtion is very different with common meaning that is ceremonial ,custom and habits. In this view point, tradition is a resource for arriving to God and includes foundations of metaphysic or ontology, sociology, morality and theology. In center of all traditions is Sophia Perennis, but schuon states that Sophia perennis is eguivalent with metaphysic. and metaphyic is a knowledge to supreme truth that is accessible through intellect not through reason. In nasr point of view,Sophia perennis is including of metaphysic that confirmed to the recognition of Principle. Against view point of Huxley that using term of Sophia perennis states by Laibnits For the first time ,He belived that this term is used by Agostino Stivco for the first time and it is as a work form Ibn moskooye in Islamic notion. Thus, regarding to nasr idea and age of Ibn moskooye and Agostino stivco life time seems that we have to state that this term is used by this muslim sage, for the first time. In this article, the main aim is the reviewing of most important foundation of traditionalist's and followers of Sophia perennis with affirmation of schuon ideas as completing of traditionalism way, Dr. nasr as commentator of his works and aspects of different and similarity two Contemporary philosopher's point of views ,until with getting a framework for recognition of origin ,dynamic and universal tradition, revealas the position of Sophia perennis in the contemporary philosophical notions.